Moringa oleifera Lam.: A Nutritional Powerhouse with Multifaceted Pharmacological and Functional Applications - Natalina Panova; Anelia Gerasimova; Galia Gentscheva; Stoyanka Nikolova; Lubomir Makedonski; Margarita Velikova; Abdessamad Beraich; Abdelmonaem Talhaoui; Nadezhda Petkova; Daniela Batovska; Krastena Nikolova (Life)
Moringa oleifera, often referred to as the “miracle tree”, has gained widespread recognition for its exceptional nutritional profile and broad pharmacological potential. This review provides a comprehensive synthesis of the plant’s botanical characteristics, taxonomy, cultivation practices, and biochemical composition. Special emphasis is placed on its rich content of bioactive secondary metabolites-such as flavonoids, alkaloids, phenolic acids, saponins, isothiocyanates, and glucosinolates-which underlie its diverse therapeutic effects. The paper compiles and analyzes evidence from over 200 peer-reviewed studies, documenting antioxidant, anti-inflammatory, antimicrobial, antidiabetic, anticancer, hepatoprotective, neuroprotective, and anti-obesity effects, among others. For instance, leaf extracts have demonstrated potent antioxidant and antidiabetic effects in both animal models and clinical trials, while seed-derived isothiocyanates have shown significant antibacterial and anticancer activity. In addition, clinical and in vivo data support M. oleifera’s role in fertility regulation, cardiovascular protection, and neurodegenerative disease mitigation. Beyond its medicinal applications, the review highlights its growing use in functional foods, dietary supplements, and cosmeceutical products, reflecting its commercial and industrial relevance. By consolidating findings across disciplines, this review underscores the multifaceted value of M. oleifera as a nutraceutical and therapeutic resource.